Pulmonary hypertension: etiology and anti-inflammatory treatment pathways of natural products - Li, Liyang; Huang, Xing; Cheng, Maojun; He, Chengxun; Dai, Changmao; Ding, Fang; Xu, Jia; Chen, Feier; Zhang, Kaichen; Li, Xueping (Frontiers in Pharmacology, 2026)
Pulmonary hypertension (PH) is a severe and progressive cardiopulmonary disorder that affects multiple organ systems. Clinically, it is manifested by progressive dyspnea, which progressively worsens with exertion and ultimately results in right heart failure and death at a late stage. Its pathological features are primarily characterized by abnormally elevated pulmonary artery pressure, pulmonary vascular remodeling, and thrombus formation. The inflammatory response is widely recognized as a key initiating factor and critical component in the progression of PH. Furthermore, therapeutic interventions are hampered by the irreversibility of vascular remodeling, high treatment expense, and hepatotoxicity induced by pharmacologic agents. Therefore, it is of great importance and potential to develop novel therapies with multi-targeted, safe, efficacious, and low-cost characteristics. Emerging evidence has demonstrated that natural products (NPs) possess remarkable potential in modulating pulmonary vascular remodeling (PVR) and right ventricular function, and their effects may be associated with inflammation. In this review, we comprehensively review recent advances in the use of NPs to ameliorate PH by modulating inflammation-associated signaling pathways, highlighting the crucial role of inflammation in PH pathogenesis. We attempt to provide a theoretical basis and research strategy for using inflammatory approaches with natural products in PH, which would be helpful for the development of novel therapies.